(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Over the last couple of decades Teaching-Learning of Foreign Language has come up with the possibilities and opportunities for all age groups across India and has become an indispensible part of Educational Institutions. Not only the students but as well the parents and the professionals too are showing their keen interest in Teaching-Learning of Foreign Language as it enhances their overall skills. In the mean time Teaching-Learning process has equipped with new trends and technologies to make it easier to grasp. Good command over a Foreign Language has yield dream come true opportunities by providing the scholarship to visit, to study and to work abroad. It curbs the boundaries and develops the cross cultural interest.At present Teaching Learning of Foreign Language is not confined to urban areas it has stepped forward to the rural areas too. On a platform where English as a Foreign Language poses a threat amidst the learner, new technologies and methodologies make it easier among the learners to imbibe the Foreign Language and which makes them stand on the fore front with other privileged students and explore the world with confidence.The present paper focuses on how teaching and learning has changed from teacher-centered to learner centered environment as well the importance, opportunities, and challenges in Teaching Learning of French through ICT based applications and the innovative approaches of teaching not only through English medium but as well with Hindi medium too.